Indian psychiatry and research in Pakistan - Chaudhry, Haroon Rashid (Medknow Publications, 2010)
In Asian culture, there is much stigmatization attached on having mental health problems and seeking help from a mental health expert. It is therefore, not surprising, that this stigmatization results in the refutation of the subsistence of a psychiatric problem in an individual and his family but also produces obstruction to help-seeking desires. To get a clear picture of the existence of psychiatric issues in the population, various research projects addressing psychiatric issues in children, women, and elderly are conducted both in Pakistan and India. A significant input has been taken from research conducted in India combating disaster management. In addition, public awareness programs are organized to provide information about common psychiatric disorders in children, adults, women, and the elderly.-Furthermore, psychiatric patients and their families are educated for the management of mental heath problems related to marriage, pregnancy, birth and hazards of smoking & substance abuse in young adults. Keeping in view the similarity in cultural background, treatment models, family structure, and psychosocial factors, collaborative research studies should be encouraged leading to improvement in psychiatric care of the patients both in India and Pakistan.